Osnove in možnosti fotodinamičnega zdravljenja - Japelj, Boštjan (Farmacevtski vestnik, 2006)
Photodynamic therapy is the treatment by the use of visible or near infrared light, which activates the photosensitizer and forms singlet oxygen. Singlet oxygen then causes damage to the living system. Photodynamic therapy is localized, as treatment is achived only in the areas which are illuminated by the light of certain wavelength. Drugs which are used as photosensitizers activate oxygen by the mechanism of electron or energy transfer.
Keywords: fotodinamično zdravljenje; fotosenzibilizator; fototerapija; prenos elektrona; prenos energije; singletni kisik